ダイ 28 ジ ナンキョク チイキ カンソク タイ キショウ ブモン ホウコク 1987 - 金戸, 進; カネト, ススム; 菅原, 英敏; スガワラ, ヒデトシ; 荻原, 裕之; オギワラ, ヒロユキ; 山本, 哲; ヤマモト, アキラ; Kaneto, Susumu; Sugawara, Hidetoshi; Ogiwara, Hiroyuki; Yamamoto, Akira (1990)
P(論文) この報告は, 第28次南極地域観測隊越冬隊気象部門が, 1987年2月1日から1988年1月31日までの期間, 昭和基地において行った気象観測(主として地上, 高層およびオゾン観測)の結果をまとめたものである。観測方法, 設備などは第27次観測隊とほぼ同じである。総合自動気象観測装置(AMOS)による地上および高層気象観測, 統計は順調に行われた, オゾンホール現象解明のため, ドブソン分光光度計およびオゾンゾンデによるオゾン観測を強化した。越冬期間中特記される気象現象としては, 次のものがあげられる。1)冬期間を除いて月平均気温は平年より高かった。また, 風は冬期間を除いて強く, 11月の平均風速はこれまでで最大となった。2)ブリザードは14回襲来したが, 6月中旬から9月中旬にかけてはブリザードがなかった。年間ブリザード回数および日数はこれまでの最少となった。3)対流圏の気温はほぼ平年より高く経過した。成層圏の気温は全般に平年より低く, 特に10月から11月にかけては平年を10℃も下回る層があった。極夜ジェットが弱まるのは通常は11月であるのに, 1ヵ月おくれて12月となった。4)オゾン全量は異常に減少し, 10月8日には153m atm-cmとこれまでの最少値を記録した。このとき成層圏下部のオゾン層の中間部分にオゾンがほとんどない層が出現した。 This paper describes the results of meteorological observations (mainly surface, upper air and ozone) from 1 February 1987 to 31 January 1988 at Syowa Station, carried out by Meteorological Observation Team of the 28th Japanese Antarctic Research Expedition. Observations and statistics of the surface and aerological data were automatically processed with the AMOS (Automated Meteorological Observation System), same as by the 27th Observation Team. Special observations of ozone were done for the ozone-hole phenomenon, using Dobson spectrophotometer and ozonesondes. Remarkable characteristics are as follows : 1) The monthly mean temperatures of all seasons except winter are higher than the normal temperature. The monthly mean wind speeds of all seasons except winter were high, especialy in November 1987 when the strongest wind was recorded. 2) Fourteen blizzards were encountered, but no blizzards from mid-June to mid-September 1987. The number and the days of blizzard in 1987 were the least record. 3) At troposphere, temperature was almost over the normal. At stratosphere, temperature was almost lower than normal and especialy from October to November the difference reached 10℃. Polar night jet stream ended in December, while normally changing in November. 4) Total ozone was depressed extraordinarily and reached 153m atm-cm on 8 October 1987. The ozone layer was separated into two peaks and between them the ozone-poor layer ...